Austronea patersoniae (Asparagaceae, Scilloideae), a new species from the Eastern Cape Province in South Africa - Martínez-Azorín, Mario; Dold, Anthony P.; Crespo, Manuel B. (Phytotaxa, 2019)
Our fieldwork in the Eastern Cape province of South Africa revealed an undescribed species of Austronea which was named by Schonland as “Urginea Patersoniae Schonl. Ms.”, but never validly published. We here describe Austronea patersoniae to include plants showing bulbs with loose scales; 5–9 narrowly linear erect leaves with papillate margins; elongate peduncle; lowermost bracts with a broad, flat, papery spur and reddish flowers with papillate filaments. We provide a complete morphological description as well as data on ecology and distribution.